하천과정과 식생 - 연구동향과 시사점 - 우효섭(Hyoseop Woo); 조강현(Kang-Hyun Cho); 장창래(Chang Lae Jang); 이찬주(Chan Joo Lee) (Ecology and Resilient Infrastructure, 2019)
We've reviewed existing studies on the interactions among vegetation, hydrology, and geomorphology in the stream corridors, adding one more factor of vegetation in the traditional area of hydro-geomorphology. Understanding of the interactions among those three factors is important not only academically but also practically since it is related intimately to the restoration of river corridor as well as management itself. Studies of this area started from field investigations in the latter part of the 20th century and focused on the flume experiments and then computer modelling in the 1990s and 2000s. Now, it has turned again to the field investigations of specific phenomena of the vegetative-hydrologic-geomorphologic interactions in detailed micro scales. Relevant studies in Korea, however, seem to be uncommon and far behind the international status quo in spite that practically important issues related directly to this topic have been emerged. In this study, we propose, based on the extensive literature review and authors' own knowledge and experiences, a conceptual diagram expressing the interactions among vegetation, flow (water), sediment, and geomorphology. Existing relevant studies in Korea since the 1990s are classified according to the categorization in the proposed diagrams and then briefly reviewed. Finally, considering the practical issues of riparian vegetation that have emerged recently in Korea, we propose areas of investigation needed in near future such as, among others, long-term and systematic field investigations and monitoring at multiple river corridors having different attributes on vegetative-hydrologic-geomorphologic interactions, including vegetative dynamics for succession. 본 연구는 전통적 수문지형학 범주에서 식생요소를 추가하여 식생-수문-지형 간의 상호작용을 연구한 국내외 성과를 정리, 분석한 것이다. 이 분야는 전통적 하천관리는 물론 하천복원과도 직접적으로 관련되어 있어 학술적으로나 실무적으로나 중요하다. 이 분야 연구는 20세기 중후 반부터 시작하여 현지조사-실내실험/수치모형의 단계를 거쳐 21세기 들어 다시 현장에서 정밀, 장기조사 단계로 가고 있다. 그러나 이 분야 국내 관련연구는 매우 미흡하다. 본 연구는 국내외 관련 연구성과를 분석하고 저자들의 지식과 경험을 토대로 식생-수문-지형 간 상호작용을 설명하는 개념적 모형과 그에 따른 6개의 유형을 제안하였다. 국내 관련연구는 제안된 6개 유형에 따라 분류하고 검토하였다. 다음 국내에서 실제 나타나는 하천식생 관련이슈들을 고려하여 향후 시급히 필요한 연구로서 식생-수문-지형 간 상호작용의 이해를 위해 특성이 서로 다른 복수의 하천에서 이에 대한 장기적, 체계적, 집중적 조사연구(모니터링) 등 다수를 제안하였다.